The Impact of Child Abuse and Dissociation on Psychiatric Comorbidity and Self-Concealment Among Prisoners in China - Chung, Man Cheung (Journal of interpersonal violence, 2022)
Child abuse is a common experience among prisoners in China and associated with elevated psychiatric comorbidity. However, the association between child abuse profiles and dissociation is unclear. The extent to which the relationship between these profiles and dissociation might influence psychiatric comorbidity and self-concealment is also unclear. This study examined the impact of this relationship on the preceding outcomes among prisoners in China using Latent Class Analysis. Four hundred and ninety-six male prisoners from China completed questionnaires measuring child abuse, dissociation, self-concealment, and psychiatric comorbidity. A three-class solution was achieved: Class 1 (neglected with moderate dissociation) prisoners had a minimal level of abuse, the highest level of neglect experience, and a medium level of dissociation; Class 2 (low neglect with low dissociation) prisoners also had a minimal level of abuse but lower levels of neglect experience and dissociation; Class 3 (abused and neglected with high dissociation) prisoners had high levels of child abuse, neglect, and dissociation. Controlling for age, Class 3 reported significantly higher psychiatric comorbidity and self-concealment than the other two classes. Class 1 was more depressed than Class 2; Class 2 was more likely to engage in self-concealment than Class 1. To conclude, the kinds of childhood maltreatment experienced by prisoners and their readiness to detach from distressing emotions can influence the severity of current distress symptoms and the tendency to conceal things about themselves.